Teamwork among Students in Business Administration Courses: utopia? - Costa, Filipe Campelo Xavier da (Review of Business Management, 2007)
From the research presented by McCorkle et al. (1999) among undergraduate business students in U.S. universities, a research among students from Brazilian private universities was developed to assess their perception about teamwork as a pedagogical tool. The benefits and shortcomings are discussed, as well compared to the results from the U.S. environment. Key-words: Business teaching. Teamwork.